2020
DOI: 10.1186/s12933-020-01161-x
|View full text |Cite
|
Sign up to set email alerts
|

Serum alkaline phosphatase levels and the risk of new-onset diabetes in hypertensive adults

Abstract: Background The association between alkaline phosphatase (ALP) and incident diabetes remains uncertain. Our study aimed to investigate the prospective relation of serum ALP with the risk of new-onset diabetes, and explore possible effect modifiers, in hypertensive adults. Methods A total 14,393 hypertensive patients with available ALP measurements and without diabetes and liver disease at baseline were included from the China Stroke P… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 47 publications
2
12
0
Order By: Relevance
“…We strongly believe that IAPD as an independent risk factor plays a pivotal role in the pathogenesis of T2DM in humans based on the following findings of our previous and current studies: (1) IAPD (IAP gene knockout) causes diabetes (hyperglycemia) in mice; (2) chronic inhibition of intestinal luminal IAP activity in mice by oral supplementation of phenylalanine, an inhibitor of IAP, in drinking water causes diabetes; (3) chronic oral supplementation of IAP prevents diabetes in IAP knockout mice; (4) IAPD is directly associated with T2DM in humans; (5) overall incidence rate of T2DM is approximately 4.2-fold higher in humans with IAPD; (6) overall relative risk of developing T2DM is increased by approximately 3.7-fold in humans with IAPD; (7) the lower the persistent IAP level the higher (approximately 16.1-fold) the incidence rate of T2DM in humans; (8) the lower the persistent IAP level the higher (approximately 13.8-fold) the relative risk of developing T2DM in humans; (9) the lower the persistent IAP level the higher (approximately twofold) the rate of increase of fasting glycemia in humans; and (10) remission of IAPD prevents T2DM in humans, as shown in this study and in Malo7 and Kaliannan et al 12. It is to note that an association between high serum alkaline phosphatase (liver/bone/kidney alkaline phosphatase) and new-onset T2DM has been reported in a population with hypertension 16. Serum alkaline phosphatase is a proinflammatory marker and we think increased serum alkaline phosphatase might indicate IAPD-induced systemic inflammation in this patient population.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…We strongly believe that IAPD as an independent risk factor plays a pivotal role in the pathogenesis of T2DM in humans based on the following findings of our previous and current studies: (1) IAPD (IAP gene knockout) causes diabetes (hyperglycemia) in mice; (2) chronic inhibition of intestinal luminal IAP activity in mice by oral supplementation of phenylalanine, an inhibitor of IAP, in drinking water causes diabetes; (3) chronic oral supplementation of IAP prevents diabetes in IAP knockout mice; (4) IAPD is directly associated with T2DM in humans; (5) overall incidence rate of T2DM is approximately 4.2-fold higher in humans with IAPD; (6) overall relative risk of developing T2DM is increased by approximately 3.7-fold in humans with IAPD; (7) the lower the persistent IAP level the higher (approximately 16.1-fold) the incidence rate of T2DM in humans; (8) the lower the persistent IAP level the higher (approximately 13.8-fold) the relative risk of developing T2DM in humans; (9) the lower the persistent IAP level the higher (approximately twofold) the rate of increase of fasting glycemia in humans; and (10) remission of IAPD prevents T2DM in humans, as shown in this study and in Malo7 and Kaliannan et al 12. It is to note that an association between high serum alkaline phosphatase (liver/bone/kidney alkaline phosphatase) and new-onset T2DM has been reported in a population with hypertension 16. Serum alkaline phosphatase is a proinflammatory marker and we think increased serum alkaline phosphatase might indicate IAPD-induced systemic inflammation in this patient population.…”
Section: Discussionsupporting
confidence: 67%
“…(2) chronic inhibition of intestinal luminal IAP activity in mice by oral supplementation of phenylalanine, an inhibitor of IAP, in drinking water causes diabetes; (3) (8) the lower the persistent IAP level the higher (approximately 13.8-fold) the relative risk of developing T2DM in humans; (9) the lower the persistent IAP level the higher (approximately twofold) the rate of increase of fasting glycemia in humans; and (10) remission of IAPD prevents T2DM in humans, as shown in this study and in Malo 7 and Kaliannan et al 12 It is to note that an association between high serum alkaline phosphatase (liver/ bone/kidney alkaline phosphatase) and new-onset T2DM has been reported in a population with hypertension. 16 Serum alkaline phosphatase is a proinflammatory marker and we think increased serum alkaline phosphatase might indicate IAPD-induced systemic inflammation in this patient population. Based on this study and other published data, we developed a model depicting the molecular mechanisms of IAPD-mediated diabetes pathogenesis (figure 4).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…28 Previous studies have shown that hypertension is closely associated with the circulating levels of blood lipids, glucose, and GHb. [29][30][31] In addition, the close association between hypertension and the levels of serum leptin and adiponectin in aging populations was also reported. However, we did not detect a significant link between hypertension and any of the above-mentioned factors, although hypertension was closely related to obesity.…”
Section: Dovepressmentioning
confidence: 87%
“…Alkaline phosphatase (ALP) can catalyze the cleavage of various phosphates in alkaline environments and is responsible for the phosphorylation and dephosphorylation of phosphate-containing molecules in organisms. 1 The activity of ALP is closely related to many diseases, such as cancer, 2 diabetes, 3 bone disease, 4 hepatobiliary disease, 5 etc . The development of a simple and sensitive ALP detection method is of vital importance.…”
Section: Introductionmentioning
confidence: 99%